2012
DOI: 10.1074/jbc.m112.358911
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Submicromolar H2O2 Levels Induce Hepcidin via Signal Transducer and Activator of Transcription 3 (STAT3)

Abstract: Background: Hepcidin, the systemic iron regulator, is induced during inflammation and leads to low circulating and increased intracellular iron levels. Results: (Patho)physiologically relevant H 2 O 2 levels up-regulate hepcidin via STAT3 in cultured liver cells. Conclusion: Intracellular and extracellular H 2 O 2 acts similarly to IL-6 on hepcidin up-regulation and requires a functional STAT3-binding site. Significance: H 2 O 2 is an important link between inflammation and iron metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
89
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(92 citation statements)
references
References 47 publications
1
89
0
2
Order By: Relevance
“…A recent study demonstrated in vitro that sustained levels of H 2 O 2 , similar to inflammatory conditions, are sufficient to activate hepcidin transcription in hepatocytes via increased STAT-3 phosphorylation. 48 The authors further found that H 2 O 2 acts synergistically with IL-6 in inducing hepcidin, thus suggesting another mechanism through which oxidative stress contributes to the anemia of chronic disease. 48 To strengthen our results we compared anemic and nonanemic patients, confirming that anemia was significantly associated with the highest levels of CRP, inflammatory cytokines, EPO, ferritin, hepcidin and ROS levels, and with the lowest levels of serum iron, transferrin, leptin, albumin, lipid profile parameters and antioxidant Role of inflammation and malnutrition in CRA haematologica | 2015; 100 (1) 129 enzymes.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A recent study demonstrated in vitro that sustained levels of H 2 O 2 , similar to inflammatory conditions, are sufficient to activate hepcidin transcription in hepatocytes via increased STAT-3 phosphorylation. 48 The authors further found that H 2 O 2 acts synergistically with IL-6 in inducing hepcidin, thus suggesting another mechanism through which oxidative stress contributes to the anemia of chronic disease. 48 To strengthen our results we compared anemic and nonanemic patients, confirming that anemia was significantly associated with the highest levels of CRP, inflammatory cytokines, EPO, ferritin, hepcidin and ROS levels, and with the lowest levels of serum iron, transferrin, leptin, albumin, lipid profile parameters and antioxidant Role of inflammation and malnutrition in CRA haematologica | 2015; 100 (1) 129 enzymes.…”
Section: Discussionmentioning
confidence: 95%
“…A recent study demonstrated in vitro that sustained levels of H 2 O 2 , similar to inflammatory conditions, are sufficient to activate hepcidin transcription in hepatocytes via increased STAT-3 phosphorylation. 48 The authors further found that H 2 O 2 acts synergistically with IL-6 in inducing hepcidin, thus suggesting another mechanism through which oxidative stress contributes to the anemia of chronic disease. …”
mentioning
confidence: 95%
“…Finally, upon infection, activated inflammatory cells undergo an oxidative burst that results in the release of large amounts of reactive oxygen species, which help to kill invading microbes. Neutrophils generate H 2 O 2 when activated, and work in cell culture has shown that low levels of H 2 O 2 stimulation contribute to hepatic hepcidin induction through STAT3 (55).…”
Section: Regulation Of Hepcidin By Inflammationmentioning
confidence: 99%
“…Авторами были про-ведены эксперименты с использованием двух способов доступа к окислительному стрессу: лечение клеток с Н2О2 или Ар-42 пептида в его олигомерной форме. Оба вида лечения вызвали накопление маркеров окислительного стресса, такие как окис-ленные белки и липиды, а также измене-ния в ДНК, что также отмечали Millonig G., Gansleben I., Peccerella T. et al [11]. Что ка-сается микроэлементов, клетки, обработан-ные Н2О2, показали более высокие уров-ни Zn и более низких уровней Са в ядрах по сравнению с контрольными клетками, без каких-либо окислительных обработок.…”
Section: международный журнал прикладныхunclassified
“…В астроцитах интерлейкин-lfl повышает генерацию Н 2 О 2 , что приводит к снижению фосфатазной ак-тивности и активации МАР-киназы. ФНО-а через повышение образования АФК активи-рует факторы транскрипции NF-kp и АР-1, процессы апоптоза [11,23].…”
Section: заключениеunclassified